CONSTRUCTAL LAW AND THE OGP OPTIMAL GLOBAL PRICING TECHNOLOGY (14th CONSTRUCTAL LAW CONFERENCE | 10-11 October 2024, Bucharest, Romania, 2024)
The document discusses the integration of physics with economics through OGP technology and its application in resolving market arbitrage in various industries.
Keywords: Electrical circuits equilibrium; Economic systems equilibrium; Optimal solutions